2009
DOI: 10.1016/j.chom.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Two Mosquito LRR Proteins Function as Complement Control Factors in the TEP1-Mediated Killing of Plasmodium

Abstract: Plasmodium development within Anopheles mosquitoes is a vulnerable step in the parasite transmission cycle, and targeting this step represents a promising strategy for malaria control. The thioester-containing complement-like protein TEP1 and two leucine-rich repeat (LRR) proteins, LRIM1 and APL1, have been identified as major mosquito factors that regulate parasite loads. Here, we show that LRIM1 and APL1 are required for binding of TEP1 to parasites. RNAi silencing of the LRR-encoding genes results in deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
263
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(272 citation statements)
references
References 31 publications
9
263
0
Order By: Relevance
“…In fact, the mature TEP1 protein must physically interact with two leucine-rich repeat proteins (APL1 and LRIM1) encoded by genes on an independent chromosome, 2L (32,33). Thus, efficiency of parasite binding and killing may be a function of polymorphisms in TEP1 itself, and/or in APL1, LRIM1, or other proteins that control its function.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the mature TEP1 protein must physically interact with two leucine-rich repeat proteins (APL1 and LRIM1) encoded by genes on an independent chromosome, 2L (32,33). Thus, efficiency of parasite binding and killing may be a function of polymorphisms in TEP1 itself, and/or in APL1, LRIM1, or other proteins that control its function.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that the malaria vector Anopheles gambiae defends itself against invading Plasmodium parasites by activating a complement‐like pathway with the complement C3‐like protein TEP1, which is responsible for the killing and clearance through lysis and melanization of Plasmodium ookinetes that traverse the midgut epithelium (Blandin et al ., 2004; Fraiture et al ., 2009; Povelones et al ., 2011). TEP1 is secreted into the hemolymph by the phagocytic hemocytes and knockdown of TEP1 leads to a fivefold increase of developing oocysts.…”
Section: The Effect Of Midgut Factors On Parasite Developmentmentioning
confidence: 99%
“…TEP1 is secreted into the hemolymph by the phagocytic hemocytes and knockdown of TEP1 leads to a fivefold increase of developing oocysts. For the binding of TEP1 to the parasite surface, two members of the LRR protein family, LRIM1 and APL1C, are required, which form a disulfide‐bonded complex (Fraiture et al ., 2009; Povelones et al ., 2011). This complex helps to stabilize and promote the binding of a proteolytically cleaved mature TEP1 (Povelones et al ., 2011).…”
Section: The Effect Of Midgut Factors On Parasite Developmentmentioning
confidence: 99%
“…Constitutive cleavage is observed in the hemolymph within a protease-sensitive region similar to that of C3. Proteolysis of TEP1 in the protease-sensitive region in vitro does not appear to cause a conformational change, and the thioester remains present in the resulting cleaved form of TEP1 (13), referred to here as TEP1 cut , implying that additional factors regulate activation of TEP1 in vivo..Two leucine-rich repeat (LRR) proteins were recently shown to control the function of TEP1 in A. gambiae (13,14). LeucineRich Immune Molecule 1 (LRIM1) was initially identified as having an antimalarial phenotype within the P. berghei model system and also as a factor required for efficient phagocytosis of Gram-negative but not Gram-positive bacteria (15-17).…”
mentioning
confidence: 99%
“…Two leucine-rich repeat (LRR) proteins were recently shown to control the function of TEP1 in A. gambiae (13,14). LeucineRich Immune Molecule 1 (LRIM1) was initially identified as having an antimalarial phenotype within the P. berghei model system and also as a factor required for efficient phagocytosis of Gram-negative but not Gram-positive bacteria (15-17).…”
mentioning
confidence: 99%